Seed and Germination Study of a New Guinea Endemic Plant Species Grevillea papuana Diels. - Farid Kuswantoro (Universitas Gadjah Mada, 2021)
Grevillea papuana is a culturally important endemic plant species of New Guinea highland. Although G. papuana conservation and propagation attempts were already conducted, this species seed and germination characters information were still very limited. This study aimed to provide information regarding G. papuana seed and germination biology. Seed characteristic and germination trials were conducted in this study. Data analysis was conducted descriptively, while germination parameters were also calculated. G. papuana has a light, elliptic, and winged seed. The species germination was low and ununiform with phanerocotylar epigeal foliaceous (PEF) seedling functional type.